SURFACE STRATEGY TAXONOMY ANALYSIS IN STUDENTS’ PRESENTATION USING MIND MAPPING - Ni Luh Desy Suari Dewi; Gek Wulan Novi Utami; I Gede Neil Prajamukti Wardhana (STKIP Persada Khatulistiwa Sintang, 2021)
Presentations that consist of many sentences, causing students to be unable to develop their use of language. They prefer to read rather than to explain the material by using their own words. This will affect the students' speaking skills. Therefore, this study discusses the students' language used in a presentation by using mind mapping. By using a mind mapping strategy, students are not able to write down all the sentences they present. They only write down the important points of the material so they have to try to make their sentences to explain their material. This research was conducted in two cycles. The data obtained were analyzed based on the theory of surface strategy taxonomy and it was explained descriptively qualitatively. The results showed that the grammatical errors made by students in their presentations using the mind mapping strategy were in the category of omission, addition, misformation and misordering.Keywords: Mind mapping; speaking skill; surface strategy taxonomy